IMPROVING THE RESULTS OF LEARNING ‘CATHOLIC RELIGIOUS EDUCATION’ THROUGH THE IMPLEMENTATION OF THE STUDENT TEAMS ACHIEVMENT DIVISION TYPE COOPERATIVE MODEL (STAD) MAIN MATERIALS 'CHURCH SOCIAL TEACHING' IN CLASS XI IPS 1 SMAN 2 EAST KUPANG - Yulius Bera Tenawahang (Warta Pendidikan | e-Journal, 2021)
The purpose of this research is to improve the learning outcomes of "Catholicism" through the application of a cooperative model of the Student Teams Achievement Division (STAD) type, the main material of "Church Social Teaching" in Class XI IPS 1 SMAN 2 Kupang Timur. This study uses the Classroom Action Research method. The research subjects were 19 class XI IPS students in the 2015/2016 academic year (9 girls and 10 boys). The research object is student activeness and learning outcomes. The results of this research prove that the pre-cycle student activeness is at the level of 64.79%. After the learning process was carried out using the STAD cooperative model, the activeness of students increased in cycle II to 92.79%. The pre-cycle student learning outcomes showed good category 2 (10.52%) students, enough 5 (26.31%) students, less 6 (31.57%) and very less 6 (31.57%) The results of the post test cycle I showed good category 4 student learning outcomes ( 21.05%) students, only 14 (73.68%) students, less 1 (5.26%) students. Student learning outcomes in the pre-test cycle II with good categories 8 (42.10%), enough 11 (57.89%). Student learning outcomes in the post test cycle II; very good 5 (26.31%), good 14 (73.68%). Student completeness results in the pre-test cycle I; 17 (89.47%), after action cycle I, 15 (78.94%). In the pre-test cycle II there were 11 (57.89%) and, in the post test cycle II 19 (100%). The conclusion is that learning Catholicism on the main material of Church Social Teaching using the STAD cooperative model increases student activity and learning outcomes.